Development of a quick screening staining test for detecting the oxidation potential of iron sulfide-bearing aggregates for use in concrete. (March 2016) - Ramos, Violeta; Rodrigues, Andreia; Fournier, Benoît; Duchesne, Josée
Abstract: Oxidation of iron sulfide-bearing aggregates is pointed out as responsible of concrete deterioration of numerous buildings in Trois-Rivières area, Canada. Several researchers have been focusing their efforts to fully understand the mechanisms involved in such reaction and to ultimately establish accurate guidelines for the quality control of aggregates. Though this testing programme is already rather well-established, a quick staining test will allow complementing the chemical approach that serves as its initial step. This paper presents a series of attempts to define the most accurate staining method by testing the efficiency of ASTM C 641 and the Midgley test, but also by optimizing them, namely by using different oxidizing reagents. The use of 6% bleach was able to correctly identify the oxidation potential of the investigated aggregates when used as reagent in the Midgley test. Based on the observations made in staining tests, a promising temperature test was also developed.